Pengembangan Kualitas Produk UMKM Melalui Inovasi Kemasan dan Digital Marketing - Siti Sufaidah; Munawarah Munawarah; Nurul Aminah; Memey Ayu Prasastii; Devi Oktavianti (Jumat Ekonomi: Jurnal Pengabdian Masyarakat, 2022)
MSMEs are the driving force of the Indonesian economy. Unfortunately, many MSMEs still sell conventionally so that the profits are not maximized. Jatisari Hamlet, Jatiwates Village, Tembelang District, has the potential to develop MSME businesses. Unfortunately, like the problems with other MSME business actors, MSME business actors in Jatisari still use conventional marketing methods. Therefore, it is necessary to provide assistance regarding the importance of using digital media and making attractive product packaging as an effort to increase sales of MSME products. The purpose of this activity is to increase the understanding of MSME entrepreneurs regarding the importance of product design as a sales strategy and the importance of using digital media as a promotional medium and buying and selling transactions to expand market reach. This activity was carried out in Jatiwates Village on October 1 and 2, 2022 which was attended by MSME actors. The method used in this activity is Assets Based Community Development (ABCD). The results obtained from this activity are an increase in the understanding of MSME actors regarding the importance of improving product packaging and digital media as marketing media. The output generated from this activity is a digital account as a marketing medium for products and attractive product packaging. Keywords: Digital marketing; Product packaging; MSMEs; Income